Privacy, Promotion, and Platform Pitfalls: The Case of How Telegram’s Marketing Approach Inadvertently Attracted Illicit Actors - Catayoc, Rabel B (Randwick International of Social Science Journal, 2025)
ABSTRACT This paper examines how Telegram's market positioning, digital marketing strategies, and privacy-oriented business model have unintentionally created an attractive environment for criminal activities. Applying established marketing frameworks—including the Segmentation, Targeting, Positioning (STP) model and the marketing mix (4Ps: Product, Price, Place, Promotion)—alongside consumer behavior theories of trust and anonymity, this study analyzes Telegram's business practices. A comprehensive literature review on platform marketing, digital anonymity, cybersecurity, and darknet market theory provides contextual grounding within broader academic discussions. The analysis reveals that Telegram's broad market positioning, minimal governance, and emphasis on user privacy significantly facilitate criminal activities, such as identity theft, drug trafficking, and dissemination of illicit materials. The paper proposes strategic and policy recommendations emphasizing the importance of achieving a balance between safeguarding user privacy and mitigating the exploitation of digital platforms for illicit purposes. This research uniquely integrates traditional marketing frameworks and consumer behavior theories with cybersecurity literature to evaluate Telegram’s unintended role in enabling online criminal ecosystems.